Virulence properties and antimicrobial susceptibility of Shiga toxin-producing Escherichia coli strains isolated from healthy cattle from Parana State, Brazil - Pigatto, Caroline P. [UNESP]; Schocken-Iturrino, Ruben P. [UNESP]; Souza, Emanuel M.; Pedrosa, Fabio O.; Comarella, Larissa; Irino, Kinue; Kato, Maria Aide M. F.; Farah, Sonia M. S. S.; Warth, Jose F.; Fadel-Picheth, Cyntia M. T. (Natl Research Council Canada-n R C Research Press, 2008)
The presence of Shiga toxin-producing Escherichia coli (STEC) strains in feces samples of cattle was determined using the cytotoxicity assay on Vero cells and a screening PCR system to detect stx genes. The STEC isolates were sero-typed, tested for antimicrobial Susceptibility, and analyzed for virulence genes using multiplex PCR. The verocytotoxin-producing E. coli - reverse passive latex agglutination (VTEC-RPLA) assay was also used to detect Shiga toxin production. The frequency of cattle shedding STEC was 36%. The isolates belonged to 33 different serotypes. of which O10:H42, O98:H41, and O159:H21 had not previously been associated with STEC. The most frequent serotypes were ONT:H7 (10%), O22:H8 (7%) O22:H16 (7%), and ONT:H21 (7%). Most of the strains (96%) were susceptible to all antimicrobial agents tested. Shiga toxin was detected by the VTEC-RPLA assay in most (89%) of the STEC strains. The frequency of virulence markers was as follows: stx(1), 10%; stx(2), 43%; stx(1), plus stx(2), 47%; ehxA, 44%; eae, 1%; and saa, 38%. Several strains belong to serotypes associated with human disease, and most of them carried a stx(2)-type gene, suggesting that they represent a risk to human health. The screening PCR assay showed fewer false-negative results for STEC than the Vero-cell assay and is suitable for laboratory routine.
Keywords: STEC; stx genes; Virulence genes; Shiga toxin; antimicrobial susceptibility